Minat Milenial Kota Serang Dalam Berwakaf Uang Melalui Platform Digital Di Masa New Normal - Najmudin Najmudin; Isti Nuzulul Atiah; Sujai Sujai; Abdul Aziz (FEB Universitas Sultan Ageng Tirtayasa, 2022)
This study aims to determine (1). Effect of cash waqf literacy on interest in cash waqf through digital platforms. (2 Effect of trust on interest in cash waqf through digital platforms. And (3). Effect of simultaneous cash waqf literacy and trust on interest in cash waqf through digital platforms. The object of this research is the millennial community living in Serang City, Banten Province. Research methods The method used is a quantitative-descriptive method. The data collection method uses a questionnaire. The data is processed using SPSS software version 23. The data analysis uses multiple linear regression methods. The results of this study indicate that (1) cash waqf literacy has a positive and significant effect on interest in waqf money through digital platforms (2 trust has a positive and significant effect on interest in cash waqf through digital platforms. And (3) money waqf literacy and trust simultaneously have a positive and significant effect on interest in cash waqf through digital platforms. interest in cash waqf is influenced by literacy cash waqf and confidence is 32 percent, while the remaining 68 percent is influenced by other variables not examined in this study.